Penerapan Metode Design Thinking untuk Perancangan UI/UX: APIW Aplikasi Image Watermarking - Faruq Aziz; Yanto Yanto; Daniati Uki Eka Saputri (Journal of Information System Research (JOSH), 2025)
This study aims to apply the Design Thinking methodology in the design of the user interface (UI) and user experience (UX) for APIW, an image watermarking application based on invisible watermarking for copyright protection. The Design Thinking methodology is applied through five stages: Empathize, Define, Ideate, Prototype, and Test. The innovation in this research lies in the design of the UI/UX for APIW, focusing on the invisible watermarking feature that can still be verified even when the image is resized or reformatted. This study creates an intuitive interface for users without technical skills. Design evaluation using tree testing shows a success rate of 94.71% in finding the desired features, while the search system achieves 98%. Thus, this application is designed to provide ease for users in adding watermarks to their images without compromising aesthetics. This study concludes that the application of Design Thinking in the UI/UX design of APIW successfully creates a solution that is effective, intuitive, and responsive to user needs.